(untitled) (CAHIERS MAGELLANES-NS, 2024)
Artificial Intelligence (AI) has revolutionized education by enabling personalized learning experiences tailored to the individual needs of students. This paper explores the role of AI in customizing educational content, adapting learning paths, and providing targeted feedback. AI algorithms analyse student data to recommend personalized learning materials and adjust the pace and difficulty of instruction in real-time. Natural Language Processing (NLP) enhances interaction through intelligent tutoring systems, virtual assistants, and adaptive learning platforms. Ethical considerations, including privacy and fairness, are crucial in the implementation of AI-driven personalized education to ensure equitable access and optimize learning outcomes. This Paper highlights AI's potential to transform traditional education paradigms by fostering adaptive, engaging, and effective learning environments.